Are We Fragmented Yet? Measuring Geopolitical Fragmentation and Its Causal Effect - Fernández-Villaverde, Jesús,Mineyama, Tomohide,Song, Dongho (National Bureau of Economic Research, 2024)
After decades of rising global economic integration, the world economy is now fragmenting. To measure this phenomenon, we introduce an index of geopolitical fragmentation derived from various empirical indicators. This index is developed using a flexible dynamic factor model with time-varying parameters and stochastic volatility. We then employ structural vector autoregressions and local projections to assess the causal effects of changes in fragmentation. Our analysis demonstrates that increased fragmentation negatively impacts the global economy, with emerging economies suffering more than advanced ones. Notably, we document a key asymmetry: fragmentation has an immediate negative effect, while the benefits of reduced fragmentation unfold gradually. A sectoral analysis within OECD economies reveals that industries closely linked to global markets–such as manufacturing, construction, finance, and wholesale and retail trade–are adversely affected. Finally, we examine the interaction between fragmentation and the economic dynamics of regional economic blocs, highlighting significant differences in the impacts across various geopolitical blocs
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Internationale Wirtschaft; Globalisierung; Internationale Arbeitsteilung; Wirtschaftsintegration; Kausalanalyse; Geopolitik; Welt; Bayesian Analysis: General; Cross-Sectional Models; Spatial Models; Treatment Effect Models; Quantile Regressions; Social Interaction Models; General; Global Outlook; International Factor Movements and International Business; Macroeconomic Aspects of International Trade and Finance; Economic Impacts of Globalization